The impact of capital structure on firm performance: empirical evidence from Nigeria - Dada, Ajayi Oziomobo; Ghazali, Zahiruddin (2016)
This study examines the capital structure and firm performance evidence from Nigeria. The study employed a sample size of 100 non-financial firms of listed Nigerian companies in the Nigerian Stock Exchange (NSE) for a period of 2010 to 2014. The annual financial statements have been examined using a panel data approach to analyse the empirical study. However, Tobin’s Q and ROA are used as a proxy for the firm performance. It was found out that assets turnover and, tangible have a positive and significant relationship with Tobin’s Q. Also, risk maintains negative and significant relations with Tobin’s. Moreover, the age of a firm has negative and significant with ROA and Sales growth maintains positive and significant with ROA. Nonetheless, the finding of this study would go a long way to enhance the literature on capital structure and also the imperative for the non-financial companies in Nigeria in taking capital structure decisions as it is based on the most recent data cover the period of recession of 2008-2009 as being an adverse effect of recession on the Nigerian nonfinancial companies.